Non-disulfide-Bridge peptide 5.5 from the Scorpion Hadrurus gertschi Inhibits the growth of mycobacterium abscessus subsp. massiliense - Trentini, Monalisa Martins (2017)
Multi-drug resistant microorganisms have been a growing concern during the last decades due to their contribution in mortality rates worldwide. Antimicrobial peptides (AMPs) are broad spectrum antimicrobial agents that display potent microbicidal activity against a wide range of microorganisms. AMPs generally have a rapid mode of action that reduces the risk of resistance developing among pathogens. In this study, an AMP derived from scorpion venom, NDBP-5.5, was evaluated against Mycobacterium abscessus subsp. massiliense, a rapidly growing and emerging pathogen associated with healthcare infections. The minimal bactericidal concentration of NDBP-5.5, AMP quantity necessary to stop bacteria visible growth, against M. abscessus subsp. massiliense was 200 μM, a concentration that did not induce hemolysis of human red blood cells. The therapeutic index was 3.05 indicating a drug with low toxicity and therefore good clinical potential. Treatment of infected macrophages with NDBP-5.5 or clarithromycin presented similar results, reducing the bacterial load. M. abscessus subsp. massiliense-infected animals showed a decrease in the bacterial load of up to 70% when treated with NDBP-5.5. These results revealed the effective microbicidal activity of NDBP-5.5 against Mycobacterium, indicating its potential as an antimycobacterial agent.